Creating Learning Spaces Experiences from Educational Fields (Edition 1) - Broecher, Joachim (transcript Verlag, 2019)
What can we learn from a teacher's journal about working with challenging youth? Why does the Training Room Program in German schools impede the development of an empowering learning culture? What experiences transpire during a train trip to the sea with an unruly crew of school boys? Or: what happens when children plan a trip on their own? Anyone who has accumulated experiences in teaching faces creative choices when putting that legacy to paper. The author chose to use this selection of studies to illustrate formative and inspirational moments from his years as a dedicated teacher and father.